(untitled) (Medico Legal Update, 2020)
The severe acute respiratory syndrome coronavirus 2 from the family of Coronaviridae is causing coronavirus disease. This is a zoonotic disease and identified first in the Hubei Province of China. In early 2020, this disease was announced as a global pandemic. The pandemic hit the nations undiscriminating their economic and development status. Tamil Nadu, a state of India is one of the most affected in the country. In spite of various precautionary measures in controlling the pandemic, the state recorded active cases of 18,881 as of 13th June 2020. With no defined treatment to cure the disease till date, the healthcare workers along with the collective support of various departments of the state are handling the situation with an aim to end the epidemic. Almost all the sectors such as finance, business, education, etc. were affected by the pandemic. This article discusses the current countermeasures for the infection, the impact on the state and suggests a few strategies to control the spread.